На переломе (Кадеты): повести - Куприн Александр Иванович (Мировая классика, 2004)
Экземпляры: ф.16 (2004) / Инвентарный номер: 48127 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: К 92 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44